Aflatoxin M1 contamination in different Iranian cheese types: A systematic review and meta-analysis. (October 2022) - Mohammadi, Salman; Behmaram, Khosro; Keshavarzi, Majid; Saboori, Somayeh; Jafari, Abbas; Ghaffarian-Bahraman, Ali
Abstract: Meta-analysis was used to investigate the concentration and prevalence of AFM1 in different types of cheese consumed in Iran. The results demonstrated that the pooled estimated mean of AFM1 concentration in Iranian cheese was 130.65 ng kg −1 (95% CI: 110.43, 150.86), while the percentage of AFM1 positive samples were 66.56% (95% CI: 56.82, 76.30). Also, the pooled estimated mean of AFM1 levels in ripened and fresh cheese samples were 129.33 ng kg −1 (95% CI: 94.35, 164.30) and 141.88 ng kg −1 (95% CI: 89.09, 194.66), respectively. The margin of exposure (MOE) values calculated for men, women and children were 6464 (95% CI: 7647–5598), 5684 (95% CI: 6725–4923) and 2783(95% CI: 3292–2410), respectively. Given that the MOE values were less than 10, 000, the health risk of AFM1 exposure through cheese consumption is high in Iranian population.